2001
DOI: 10.1034/j.1399-0039.2001.057005486.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel HLA‐B alleles associated with antigens in the 7C CREG

Abstract: This paper describes 9 novel HLA-B locus alleles. All of the alleles carry sequence motifs observed in other HLA-B alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Comparable changes have been observed in B*2716, B*2718 and B*2723. However, the serological recognition of these alleles has not yet been described (46) .…”
Section: Discussionmentioning
confidence: 99%
“…Comparable changes have been observed in B*2716, B*2718 and B*2723. However, the serological recognition of these alleles has not yet been described (46) .…”
Section: Discussionmentioning
confidence: 99%
“…Among HLA-B alleles, B*53 and B*07 have previously been reported to be involved in recombination events; B*53:31 was identified as arisen by a gene conversion event between B*35:03:01 and B*44:02 or B*13:02 (Adamek et al 2015 ), B*07 has been reported as donor allele group for the alleles B*44:150 and B*08:79 (Balas et al 2012a , b ), but also for the allele A*23:31 that originated from an interlocus gene conversion (Lazaro et al 2012 ). Several B*07 alleles might also have been the result of a recombination event themselves, like B*07:12 , that seems to be a recombination between B*07:02 and either B*35 , 53 , or 58 , sharing intron 2 and first part of exon 3 sequences with the latter allele groups (Steiner et al 2001 ). Also within the C*03 allele group, intralocus recombination was detected, for example, the C*03:58 allele that turned out to be a hybrid of C*03:03:01 and C*01:03 (Lazaro et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…HLA‐B*07:162 is identical to HLA‐B*07:12 in exon 2 but has one nucleotide substitution at position 419 (A to C) in exon 3 (Figure A). HLA‐B*07:12 was first reported in two African Americans but was not seen among Taiwanese. On inspection of the HLA‐B sequences commonly found in Taiwanese , we found that the sequence motif at positions 353–419 of B*07:162 was also present in B*35:01:01 and B*58:01:01 (Figure A).…”
mentioning
confidence: 99%